An overview of family functioning on cyberbullying among adolescents: a conceptual paper - Nikkhooy, Reihane; Azam, Naqi Dahamat; Hasbullah, Muslihah (Fakulti Ekologi Manusia, 2023)
The prevalence of cyberbullying is higher in adolescents, which affects their psychological well-being. Thus, it is important to understand the role of family functioning in stopping young cyberbullies from wrongdoing and protecting victims. Thus, this conceptual paper aims to explore the relations between family functioning and cyberbullying in adolescents and further discuss the roles played by key aspects such as family cohesion and family communication. Also, this paper explained theoretical backgrounds that highlight how family functioning is essential to address cyberbullying in adolescents. Some future directions are discussed.